A 67-bp variable duplication in the promoter region of the ADIPOQ is associated with milk traits in Xinjiang brown cattle. Issue 7 (12th December 2022) - Liu, Tingting; Ju, Xing; Zhang, Menghua; Wei, Chen; Wang, Dan; Wang, Zhen; Lan, Xianyong; Huang, Xi-Xia
Abstract: Adiponectin, also known as ADIPOQ, is a hormone protein secreted by adipocytes. The ADIPOQ gene is expressed primarily in adipose tissue, and the encoded protein circulates in the bloodstream and has the potential to regulate both animal fat metabolism and hormone production. Our previous work uncovered a 67-bp variable duplication in the promoter region of ADIPOQ, which reduced the basal transcriptional activity of ADIPOQ in the 3T3_L1 cell and also inhibits the ADIPOQ mRNA expression in adipose tissue. Accordingly, the present study aimed to identify the relationship between the 67-bp structural variations in ADIPOQ promoter region and the milk traits of Xinjiang brown cattle (XJBC). The results revealed two genotypes, DD and ID, in the XJBC, and minor allelic frequency (MAF) for the 'I' allele was more than 1%. Moreover, the association analysis revealed that the 67-bp duplication in the promoter region of the ADIPOQ gene was significantly correlated with the 305 days of milk production volume, fat yield, and milk fat percentage in the XJBC ( p  < 0.05). These results obtained in this study suggested that the identified variable duplication could be considered as the potential genetic marker for improving milk traits of XJBC.